2013
DOI: 10.1021/ja309866m
|View full text |Cite
|
Sign up to set email alerts
|

The Energetic Difference between Synthesis of Correct and Incorrect Base Pairs Accounts for Highly Accurate DNA Replication

Abstract: To better understand the energetics of accurate DNA replication, we directly measured ΔGO for the incorporation of a nucleotide into elongating dsDNA in solution (ΔGOincorporation). Direct measurements of the energetic difference between synthesis of correct and incorrect base pairs found it to be much larger than previously believed (average ΔΔGOincorporation = 5.2±1.34 kcal mol−). Importantly, these direct measurements indicate that ΔΔGOincorporation alone can account for the energy required for highly accur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
20
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 25 publications
2
20
1
Order By: Relevance
“…Olson et al (12), using Vent pol with 12 p/t DNA configurations, found for each example that a leveling off of right and wrong incorporations occurred in the presence of high PP i concentration. The differences in the apparent K eq for each of the steady states reflected sufficiently large free energy differences to account for pol fidelity (average ΔΔG°i nc = 5.2 ± 1.34 kcal/mol), thus obviating the need for pol active-site intervention to amplify the very small free energy differences between right and wrong base pairs deduced from thermal melting studies (ΔΔG°∼ 0.3 kcal/mol).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Olson et al (12), using Vent pol with 12 p/t DNA configurations, found for each example that a leveling off of right and wrong incorporations occurred in the presence of high PP i concentration. The differences in the apparent K eq for each of the steady states reflected sufficiently large free energy differences to account for pol fidelity (average ΔΔG°i nc = 5.2 ± 1.34 kcal/mol), thus obviating the need for pol active-site intervention to amplify the very small free energy differences between right and wrong base pairs deduced from thermal melting studies (ΔΔG°∼ 0.3 kcal/mol).…”
Section: Resultsmentioning
confidence: 99%
“…Apparent values of K eq were determined and used to calculate ΔG°v alues for R and W. Free energy differences (ΔΔG°i nc ) for incorporation of R and W were found to range from 3.5 kcal/mol to 7 kcal/mol and were thus sufficient to account for pol fidelity with no need for active-site amplification, but instead apparently reflecting intrinsic properties of p/t DNAs, dNTPs, and PP i , unperturbed by presence of polymerase. It was inferred, although not directly measured, that the leveling off in incorporation profiles was caused by sufficient pyrophosphorolysis to equilibrate forward and reverse reactions for both R and W substrates (12). Although the reverse pyrophosphorolysis reaction was reported to occur for correctly paired termini, it did not enter into the analysis and was not measured for mispaired termini.…”
mentioning
confidence: 99%
See 3 more Smart Citations